Updates on Treatment of Gemcitabine-Refractory Pancreatic Adenocarcinoma - Makrilia, Nektaria; Syrigos, Kostas N; Saif, Muhammad W (JOP. Journal of the Pancreas, 2011)
Gemcitabine monotherapy and gemcitabine-based regimens are the current standard of care for locally advanced or metastatic pancreatic adenocarcinoma. However, there is still great controversy over the role of salvage chemotherapy after failure of gemcitabine. This review is an update on the 2011 American Society of Clinical Oncology (ASCO) Annual Meeting regarding the most important developments in the treatment of refractory pancreatic cancer, as they were reported in Abstracts #e14542 and #e14588. Image: S-1: an oral fluoropyrimidine.